Importance of communication and information technology and its applications in the development and integration of performance in seaports - Tarek Mohammed Attia (Renewable Energy and Sustainable Development)
Abstract: The maritime industry is a global transporter of the goods of modern globalized economies. Shipping plays a vital role in today’s economy, with over 90% of the world’s trade carried by sea[1].The efficient transportation of cargoes impact on both consumers and the global economy. In order to improve the safety and efficiency of maritime transport and the protection of the sea and marine environment, it is inevitable to use modern information and communication technologies when collecting, storing, processing, presenting and distributing relevant data and information to the participants in maritime transport. The Smart Port used information technology (IT) extensively to create a high-tech port. The key factors contributing to the success of the IT and communication infrastructure in the Smart port are the  ability to meet the changing demands of users and to keep up with the rapid developments in IT and the ability to accommodate new technology developments without having to constantly restructure. This paper presented the key issues related to navigation systems, communication networks and information technology and its applications to secure the ships and the development of business performance for the transfer and circulation of goods within the seaports with high efficiency and the impact of this on the national economy.